Scale of protection and the various types of sports mouthguard - Patrick, D. G.; van Noort, R.; Found, M. S. (British Journal of Sports Medicine, 2005)
Objectives: To present a grading system of the protection offered by various types of mouthguard, together with an indication of associated risks, in order to make athletes aware of the consequences of improper or no mouth protection.